Vocabulary Attrition among Adult English as A Foreign Language Persian Learners - Asgari, Azadeh (2009)
This study aims to investigate the attrition rate of EFL vocabulary among Iranian female and male English language learners. They are students of a University and majored in different fields (between 20 and 25 years old). This study investigated the differences between EFL attrition rate of concrete and abstract nouns, as well as the production and reception of nouns in contextualized and non-contextualized among continuing and non-continuing students across different proficiency levels. There was no treatment in this study where the researcher compared two groups on the same variables. Hence, the design of the current study is an ex-post facto. A 40-item vocabulary test which varied across two proficiency levels are used to measure rate of vocabulary attrition as the instrument of this research. In the two stages, after an interval of three months, the students are taken the same tests. The results revealed that there was no significant difference between EFL attrition rate of abstract and concrete nouns among the continuing students across different proficiency levels however this hypothesis was rejected for the non-continuing learners at intermediate and advanced proficiency level. Furthermore, the results also indicated that there was no significant difference between EFL attrition rate of production nouns among continuing and non-continuing students across different proficiency levels whereas this hypothesis is rejected for reception at advanced level. In addition, it was shown that there was no significant difference between EFL attrition rate of contextualized nouns for continuing and non-continuing students across different proficiency levels whereas there were significant differences between EFL attrition rate of non-contextualized nouns for both groups at advanced level. Likewise, this study widens the horizon of vocabulary attrition on foreign language researchers since it investigates attrition of English as a foreign language both in those who exceed the period of non-use and those who are still exposed to the language to examine whether or not the latter undergoes attrition.